2016
DOI: 10.1016/j.apjtm.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CD14-159C/T gene polymorphism and acute brucellosis risk

Abstract: The findings provided suggestive evidence of association of the CD14-159C/T gene polymorphism with susceptibility to acute brucellosis in the Iranian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 14 Genetic variants of the CD14 gene (a C-to-T transition, snp −159 C/T) have been shown to be associated with susceptibility to multiple diseases and conditions including allergic rhinitis, 15 functional dyspepsia, 16 inflammatory bowel disease, 17 gram-negative bacteria, and respiratory infections, including brucellosis. 18 21 Its significance in allergic reactions and outcome in patients with asthma have also been documented. 21 , 22 24 In human, malaria infections particularly, elevated levels of soluble CD14 have been found in patients with acute infections, 25 concluding that soluble CD14 levels may play a critical role in disease severity.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Genetic variants of the CD14 gene (a C-to-T transition, snp −159 C/T) have been shown to be associated with susceptibility to multiple diseases and conditions including allergic rhinitis, 15 functional dyspepsia, 16 inflammatory bowel disease, 17 gram-negative bacteria, and respiratory infections, including brucellosis. 18 21 Its significance in allergic reactions and outcome in patients with asthma have also been documented. 21 , 22 24 In human, malaria infections particularly, elevated levels of soluble CD14 have been found in patients with acute infections, 25 concluding that soluble CD14 levels may play a critical role in disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…is the most important virulence factor of Brucella spp., affecting entry into phagocytic cells and protecting from the immune response. 10 While cell-mediated immunity is the major mechanism for resistance to brucellosis, acquired humoral immunity also plays an important role in recovery from the disease. 1 Hypersensitivity to Brucella antigens develops synchronously with immune response, resulting in the formation of granulomas that may contribute to some of the clinical manifestations of the disease; these granulomas may participate in restraining bacterial growth as an antibacterial defense mechanism of macrophages and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the prevalence of CD14-159 TT and CT genotypes were correlated with an increased risk of brucellosis. 10 A study that questioned association of IL-17 (inflammatory cytokine, which acts as a regulator reduces releasing of interferon-gamma [IFN-γ] and increases resistance to brucellosis) gene polymorphisms and susceptibility to brucellosis, was found that the GG genotype at positions rs3748067, rs3819025, rs4711998, and AA genotype at positions rs3819024 were correlated with an increased risk against the disease. 13 IFN-γ is known as one of the main cytokines which play an important role in immunity against Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with active brucellosis have symptoms such as fever, headache, sweating, weakness, weight loss, persistent joint pain, endocarditis, neurological complications, and testicular or bone abscess formation. 4,5 Brucella spp. invade reticuloendothelial system cells and can reproduce in these cells, and escape from the host's immune system.…”
Section: Introductionmentioning
confidence: 99%